Entre religión real y religión urbana - Barraqué, Jean Pierre (En la España Medieval, 2008)
The Books of Proclamations of Zaragoza present two major series of rites. The first entails manifestations of loyalty and devotion to the person of the King and to the kingdom, following a model of monarchy comparable to the cities of southern Italy: royal entry ceremonies, prayers for the health of the King, actions of thanks for victories in the kingdom of Granada. The second constitutes a true civic religion in the practice of great urban processions and in the cult of Saint Engracia, real patron of the city, seeking protection against natural and human disasters.